2010
DOI: 10.1155/2010/562356
|View full text |Cite
|
Sign up to set email alerts
|

Increasing a Robust Antigen-Specific Cytotoxic T Lymphocyte Response by FMDV DNA Vaccination with IL-9 Expressing Construct

Abstract: Various chemokines and cytokines as adjuvants can be used to improve efficacy of DNA vaccination. In this study, we sought to investigate if a DNA construct expressing IL-9 (designed as proV-IL9) as a molecular adjuvant enhance antigen specific immune responses elicited by the pcD-VP1 DNA vaccination. Mice immunized with pcD-VP1 combined with proV-IL9 developed a strong humoral response. In addition, the coinoculation induced significant higher level of antigen-specific cell proliferation and cytotoxic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Notably, in contrast to the beneficial role of LCs described in this study, LCs of the genital mucosa were recently reported to dampen CD8 + T cell responses after immunization with a recombinant protein by a mechanism that may involve IL-17 production (45). Secretion of IL-17, however, was reported to be downregulated after plasmid DNA immunization (49,50), explaining, in some way, the differences between the buccal and genital mucosal tissues.…”
Section: Discussioncontrasting
confidence: 70%
“…Notably, in contrast to the beneficial role of LCs described in this study, LCs of the genital mucosa were recently reported to dampen CD8 + T cell responses after immunization with a recombinant protein by a mechanism that may involve IL-17 production (45). Secretion of IL-17, however, was reported to be downregulated after plasmid DNA immunization (49,50), explaining, in some way, the differences between the buccal and genital mucosal tissues.…”
Section: Discussioncontrasting
confidence: 70%
“…Tc17 cells, which produce IL-17 [42], [43], [44], [45], [46], [47], are also cytotoxic [12], [42], [48] and have been shown to protect animal against acute influenza virus infection [48]. To date, HBV specific Tc1 cells have been demonstrated to control chronic HBV infection [7], [15] and eliminate HBV infected hepatocytes in transgenic animal model [19], [20].…”
Section: Discussionmentioning
confidence: 99%
“…Tc1 cells are the classical cytotoxic T cells that produce IFN-γ and TNF-α and can destroy virally infected cells through the targeted secretion of perforin and granzymes from lytic granules [39] , [40] , [41] . Tc17 cells, which produce IL-17 [42] , [43] , [44] , [45] , [46] , [47] , are also cytotoxic [12] , [42] , [48] and have been shown to protect animal against acute influenza virus infection [48] . To date, HBV specific Tc1 cells have been demonstrated to control chronic HBV infection [7] , [15] and eliminate HBV infected hepatocytes in transgenic animal model [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukins have a crucial effect on DNA vaccine potency and enhance the immune response. For instance, IL-6 enhances the cell-mediated immune response and promotes maturation of dendritic cells and their immune function [112], IL-9 enhances the antigen-specific cytotoxic T lymphocyte response [137], IL-15 enhances mucosal and cellular immune responses and IFN-γ production induced by FMD DNA vaccines [121], IL-18 increases the immunogenicity of vaccines, CSF enhances the immune response [78], INF-α/β enhances the cell-mediated immune response and promotes maturation of dendritic cells and their immune function, INF-γ augments both cellular and humoral immune responses [104], and IL-1 and IL-2 promote antibody responses [102,131].…”
Section: Dna Vaccinesmentioning
confidence: 99%